Synthesis, structural characterization, Hirshfeld surface and DFT based reactivity, UV filter and NLO studies of Schiff base analogue of 4-aminoantipyrine - T.A. Nibila; T.K. Shameera Ahamed; P.P. Soufeena; K. Muraleedharan; Pradeepan Periyat; K.K. Aravindakshan (Results in Chemistry, 2020)
A pyrazolone based novel Schiff base, 4-(4-benzyloxybenzalidene) amino-2,3-dimethyl-1-phenyl-3-pyrazolo-5-one (L) was synthesized by appropriate synthetic route. It was characterized by elemental-, SCXRD-, FT-IR-, UV/Vis-, ESI-MS-, and Thermogravimetric analyses. Density Functional Theory (DFT) calculations were carried out to obtain the ground state optimized geometry of the molecule using the B3LYP method and the 6-311++G(d,p) Basis set. Calculated geometrical parameters and spectroscopic information agreed well with the single crystal X-ray data. Reactivity (Fukui functions), electronic properties (HOMO-LUMO) and surface properties (MEP and Hirshfeld) were also studied to establish the nature of the electrophilic- and nucleophilic sites and the interactions within the crystal structure of the compound. UV–Vis spectral- and molecular orbital distribution analyses ensured the UV filter activity of the compound. The computed hyperpolarizability showed that the compound might be used for non-linear optical (NLO) applications in the near future.